2016
DOI: 10.1515/pjfns-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Lipid Fraction of Cookies Enriched with Chokeberry Polyphenols Extract

Abstract: The effect of incorporation of different contents of chokeberry polyphenols extract (CPE) into cookie recipe on the oxidative stability of the lipid fraction of cookies was determined in the study. Margarine and butter cookies with different contents of CPE were prepared. Contents of primary (Peroxide value, PV) and secondary (Anisidine value, AV; thiobarbituric acid reactive substances, TBARS) lipid oxidation products and fatty acids profi le were measured during storage. Different course of lipid degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…1). This observation is in agreement with results of other authors who found that plant components rich in antioxidants used in formulas may act as a pro-oxidants in cookies (Bialek et al, 2016).…”
Section: Oxidative Stability Of Cookies During Storagesupporting
confidence: 94%
See 3 more Smart Citations
“…1). This observation is in agreement with results of other authors who found that plant components rich in antioxidants used in formulas may act as a pro-oxidants in cookies (Bialek et al, 2016).…”
Section: Oxidative Stability Of Cookies During Storagesupporting
confidence: 94%
“…As compared with C-samples, lower amounts of hydroperoxides were found in enriched cookies containing 0.5 to 1.5% FJQF due to the presence of phenolic and other compounds having antioxidant potential. Similar results were reported for enriched cookies and bakery products with plant components rich in antioxidants: green and yellow tea leaves, chokeberry extract, cherry pomace extract, black currant and jostaberry powder as natural ingredients to inhibit lipid oxidation (Bialek et al, 2016;Gramza-Michałowska et al, 2016;Molnar et al, 2015;Šaponjac et al, 2016). Also, substitution of wheat flour by other plant ingredients (e.g.…”
Section: Oxidative Stability Of Cookies During Storagesupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, phenolic‐rich extracts included as food ingredients might have the additional advantage of contributing with their own bioactive properties of these compounds . In this respect, diverse examples can be found in the scientific literature concerning the use of berries for antioxidant and functional purposes in foodstuffs, including meat products . However, the potential use of mortiño as an antioxidant ingredient in meat products has not been considered previously.…”
Section: Introductionmentioning
confidence: 99%